Rapid Spheroidizing Annealing via Combining Warm Deformation with Divorced Eutectoid Transformation in M50 Steel - Dongsheng Qian; Bin Chen; Feng Wang; Lingyan Wu (Metals, 2022)
In this work, a novel routine to realize the rapid spheroidizing annealing (SA) process has been proposed in M50 steel via combining warm deformation (WD) and divorced eutectoid transformation (DET). In this process, the sample is first subjected to partial austenitizing to realize the partial dissolution of carbides, then slowly cooled to DET temperature for WD. Finally, the sample is slowly cooled to below the eutectoid transformation temperature to complete the SA. The results show that an excellent spheroidized microstructure can be obtained via the rapid SA process within 2 h. The finest spheroidized carbide (0.295 μm), as well as an appropriate hardness (217 HV), is achieved when the WD and DET processes are conducted at 760 °C. This should be attributed to that the WD not only accelerates the DET but also can break the primary carbides, leading to the uniformly distributed and refined carbides. In addition, the proposed WD that realizes rapid SA shows the excellent roundness of spheroidized carbides compared with the traditional cold/hot deformation which needs a long-term SA process. This work provides a highly efficient routine to simultaneously realize the SA and shape forming, which is of great engineering significance for the manufacturing of bearings.